A Case for Improving Postal Security in the Department of Posts, India. (December 2020) - Lobo, Charles
The term 'postal security' as used here broadly refers to the measures taken by the Post Organization (Department or Company) for the safe transmission of letters and parcels of the customers from the origin to its destination. It refers to measures to protect letters and parcels from untrustworthy employees and other criminal elements. The safety and security of postal property can also be added under this definition. This article attempts to examine the postal security aspects from a narrow scope limited to the postal articles in transmission by post. It does not cover safety measures to protect postal property or banking frauds. The focus is on the customer and the protection of his consignments entrusted to the post office for transmission.